TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE: A New Pedagogical Approach in Islamic Education in the Pandemic Era - Prasetia, Senata Adi; Khalidiyah, Tuhfatul; Arif, Syaiful (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2021)
This paper proposes TPACK as a new pedagogical approach in Islamic education in the pandemic era. Pedagogical approach refers to the method and practices of a teacher. When planning a lesson, teachers consider the best way to communicate and deliver the relevant information to enable pupils the best possible learning experience. They will take into account the context of the subject and also their own teaching preferences. In this context, pedagogical approach is necessity in Islamic education in Covid-19 Pandemic Era. Therefore, no other way but teachers must integrate a technology to Islamic education called Technological Pedagogical Content Knowledge (TPACK). Because, the traditional approach of instruction does not seem able to provide solutions for most of the educational problems, especially Islamic education. As methodological approaches, we carry out a literature review complemented by a conceptual analysis based on data from the relevant journal. This paper shows that TPACK framework is built on Lee Shulman's pedagogical construction with three core elements, namely content, pedagogy, and technology. Also, this paper argues that Islamic education need to adopt TPACK as a new pedagogical approach to its learning model in the pandemic era. Developing, strengthening and mainstreaming of TPACK by Islamic education teachers is very important for effective teaching with technology. TPACK as a new pedagogical approach to Islamic education learning models in the pandemic era allows Islamic education teachers to become agents of change to promote Islamic education to be more inclusive, accommodating and adaptive to the demands of the times.